Conversion of Biowaste into Larnite by Sol‐Gel Combustion Route for Biomedical Applications. Issue 4 (24th January 2022) - Vijayakumar, Naveensubramaniam; Venkatraman, Senthil Kumar; Choudhary, Rajan; Indurkar, Abhishek; Chatterjee, Ankita; Abraham, Jayanti; Ostrovskiy, Sergey; Senatov, Fedor; Locs, Janis; Swamiappan, Sasikumar
Abstract: The conversion of waste product into a valuable material can significantly reduce the environmental pollution. In present study, eggshell waste was utilized to synthesize larnite (Ca2 SiO4 ) at 850 °C via sol‐gel assisted combustion method. TG/DSC, FT‐IR, XRD and SEM/EDX were utilized to characterize the larnite sample. The biomineralization study clearly indicates that larnite has the ability to induce apatite formation on its surface within 3 days, after immersion in the simulated body fluid medium. According to the microscopic investigation, spherical beads like morphology confirmed the apatite deposition on the surface of larnite scaffold. Also, larnite showed significant resistance against the growth of clinical pathogens at a low concentration of 2 mg/mL. The observations suggest that larnite could be used as a coating material over the inert orthopaedic implants in the field of biomedical applications. Abstract : The current work dealt with the synthesis of dicalcium silicate from the biowaste by employing sol‐gel aided combustion technique. The pure phase of larnite was achieved at a calcination temperature of 850 °C. The investigation on biomineralization ability of larnite exhibited better apatite deposition compared to the previous reports. In addition, the bactericidal activity of the larnite bioceramics showed better inhibition on the growth of gram (‐ve) strains in the bacterial culture medium.